Ionic polymer metal composites (IPMCs) : smart multi-functional materials and articial muscles. Volume 2 - Shahinpoor, Mohsen (Royal Society of Chemistry, 2016)
A comprehensive resource on ionic polymer metal composites (IPMCs) edited by the leading authority on the subject.
Keywords: Conducting polymers.; Smart materials.; elektronické knihy; electronic books